2013
DOI: 10.2174/13894501113146660216
|View full text |Cite
|
Sign up to set email alerts
|

Functions and Mechanisms of Green Tea Catechins in Regulating Bone Remodeling

Abstract: Osteoporosis is caused by an imbalance in bone remodeling, a process involving bone-building osteoblasts and bone-resorptive osteoclasts. Excessive reactive oxygen species and inflammatory responses have been shown to stimulate differentiation and function of osteoclasts while inducing osteoblast apoptosis and suppressing osteoblastic proliferation and differentiation via extracellular signal-regulated kinases (ERK), ERK-dependent nuclear factor-κB and Wnt/β-catenin signaling pathways. The anti-oxidant and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…A broad spectrum of the TGF- β family effects on the bone tissue is also visible in a direct effect on its metabolism, involving continuous resorption and synthesis of bone structures [ 181 ]. A disturbance of a subtle balance of these processes results in osteoporosis (OP), disease related to reduced bone mineral density (BMD) [ 221 ]. Significantly increased risk of fractures and possible complications during the fracture healing process are factors inseparably related to and correlated with osteoporosis [ 222 , 223 ].…”
Section: Potential Role Of Tgf- β Family In Framentioning
confidence: 99%
“…A broad spectrum of the TGF- β family effects on the bone tissue is also visible in a direct effect on its metabolism, involving continuous resorption and synthesis of bone structures [ 181 ]. A disturbance of a subtle balance of these processes results in osteoporosis (OP), disease related to reduced bone mineral density (BMD) [ 221 ]. Significantly increased risk of fractures and possible complications during the fracture healing process are factors inseparably related to and correlated with osteoporosis [ 222 , 223 ].…”
Section: Potential Role Of Tgf- β Family In Framentioning
confidence: 99%
“…(-)-Epigallocatechin-3-gallate (EGCG) is widely studied because of its potent antioxidant effects [7]. Previous animal studies found that green tea polyphenol extracts improved several bone loss models related to aging, estrogen-deficiency, and chronic inflammation [8][9][10][11][12][13][14]. Although Numerous clinical and animal studies indicated that tea can increase bone volume and diminish osteoporotic fractures, the relationship between tea consumption and fracture healing remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…EGCG stimulates mesenchymal stem cells directing them to osteogenic lineage by means of MAPK/ ERK (mitogen activated protein kinase/extracellular signalregulated kinases) suppression and induction of PP2A (protein phosphatase 2A), increasing alkaline phosphatase activity as well as the expression Runx2, ALP, OPN and OC genes. This catechin also suppresses adipocyte differentiation and induces its apoptosis, beta-oxidation of fatty acids and lipolysis (Shen et al, 2013). In agreement with Jin et al (2014), EGCG is capable to direct osteogenic differentiation by continuous regulation of Runx2, besides modulating bone morphogenetic protein 2 (Bmp2).…”
Section: Quantitative Analysismentioning
confidence: 71%